THE EFFECTIVENESS OF LEARNING MODELS REALISTIC MATHEMATICS EDUCATION AND PROBLEM BASED LEARNING TOWARD MATHEMATICAL REASONING SKILLS AT STUDENTS OF JUNIOR HIGH SCHOOL - Ahmad Rustam; Gemi Susanti (USN Kolaka, 2018)
This research aims to analyze the difference effectiveness of learning model Realistic Mathematics Education (RME) and model learning problem based learning (PBL) to students' mathematical reasoning skills. The design of this research is quasi experiment with pretest-posttest control group design. The population of this study is the students of gradeVIII SMPN 1 Watubangga 2015/2016 year that studying about building a flat side space. The data of mathematical reasoning skills is obtained by using the instrument in the form of mathematical reasoning test. Data analysis technique used is descriptive statistical analysis, F test with t test (paired-samples t test and independent-samples t test), at ? = 0,05 . Basedon the result of analysis of research data obtained that: 1). Student's mathematical reasoning skills before being taught with RME, PBL, and Direct learning models are in the less category after being given learning with the learning model RME, PBL and Direct students' mathematical reasoning skills are in sufficient category. Increased students' mathematicalreasoning skills are in the medium category; 2). There is an improvement in students' mathematical reasoning skills after being taught with RME, PBL and Direct learning models; 3). The mathematical reasoning skills of students taught using the RME learning model were not significantly different from those taught by the PBL learning model; 4). There is adifference in the effectiveness of the learning model on improving students' mathematical reasoning skills, which is taught using a learning model RME more effective than students taught by direct learning model; 5). The students' mathematical reasoning skills are taught using the PBL learning model more effective than students taught by direct learning model;6). Student activity during learning process using RME learning model and PBL learning models, indicating that students are very active.